About the influence of wheel-rail adhesion on the maximum speed of trains - Spiroiu Marius-Adrian (MATEC Web of Conferences, 2018)
Wheel-rail adhesion is a fundamental aspect in rail transport, with high impact on traction and braking of trains. In the case of high speeds trains, wheel-rail adhesion is particularly important, as the maximum usable traction force is limited by the adhesion force. The present paper analyses the influence of wheel-rail adhesion on the maximum speed of trains, considering ranges of usual values for the track gradient and the adhesion coefficient and the real data of two Japanese high-speed trains. Analysis shows that low adhesion and high track gradient result in significant reduction of train speed.